2006
DOI: 10.2166/wh.2006.0015
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient removal from septic effluents as affected by soil thickness and texture

Abstract: This study evaluated the effectiveness of soils with different textures and thickness to treat BOD, N and P eluted from household septic effluent. The assessments were accomplished by leaching undisturbed soil monoliths of 30, 45 and 60 cm thickness and 25 cm in diameter, representing the four different textural groups and hydraulic loadings recommended by the Kentucky Health Department, with domestic wastewater effluent collected regularly from a household septic system. Effluent concentrations were monitored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Karathanasis et al (2006) that found finer textured soils (clay loams and clays) were more efficient at reducing NH 4 , total N and BOD than coarse textured soils, due to more reactive surface areas and greater nitrification/ denitrification potential.CONCLUSIONSOSWWS in soil groups I and II were less effective at DIN removal as compared to systems in soil group III.OSWWS installed in soil groups II with 30 cm of separation distance and in soil group I with 45 cm of separation distance consistently contributed septic effluent with elevated NH 4 þ -N concentrations to the shallow groundwater. The shallow groundwater in coastal North Carolina is connected to the adjacent surface waters and such pollutant loading may contribute to eutrophication and fish kills.…”
mentioning
confidence: 90%
“…Karathanasis et al (2006) that found finer textured soils (clay loams and clays) were more efficient at reducing NH 4 , total N and BOD than coarse textured soils, due to more reactive surface areas and greater nitrification/ denitrification potential.CONCLUSIONSOSWWS in soil groups I and II were less effective at DIN removal as compared to systems in soil group III.OSWWS installed in soil groups II with 30 cm of separation distance and in soil group I with 45 cm of separation distance consistently contributed septic effluent with elevated NH 4 þ -N concentrations to the shallow groundwater. The shallow groundwater in coastal North Carolina is connected to the adjacent surface waters and such pollutant loading may contribute to eutrophication and fish kills.…”
mentioning
confidence: 90%
“…Although numerous studies have focused on the effects of soil type and groundwater depth on OWTS N treatment (Cogger and Carlile 1984; Karathanasis et al 2006; Humphrey et al 2010a) few studies have focused on the effects of meteorological conditions on OWTS N treatment in coastal settings. Arnade (1999) looked at the effects of increased summer rainfall patterns and shallow water tables on groundwater NO 3 − -N concentrations in Palm Bay, FL.…”
Section: Introductionmentioning
confidence: 99%
“…Soil texture and depth also were also determined to be important for removal of fecal bacteria from septic effluents (Karathanasis et al, 2006b). The recommended separation of 30 cm between the bottom of the drain field and a limiting soil interface was generally inadequate for removing coliforms, especially for coarser soils.…”
Section: Szna Sustainable?mentioning
confidence: 99%